2017
DOI: 10.1007/s11745-017-4302-x
|View full text |Cite
|
Sign up to set email alerts
|

PAM, OLA, and LNA are Differentially Taken Up and Trafficked Via Different Metabolic Pathways in Porcine Adipocytes

Abstract: Dietary fatty acids have different effects on fat deposition in pigs. To clarify the underlying mechanisms of this difference, we compared the metabolism of palmitic (PAM, saturated), oleic (OLA, monounsaturated) and linoleic acid (LNA, polyunsaturated) in porcine adipocytes treated with 100 μM PAM, OLA or LNA. We observed that the adipocytes incubated with LNA accumulated more lipids compared with those treated with PAM and OLA. We then probed the metabolism of these fatty acids in porcine adipocytes by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In this study, we found that OA increased the protein expression of the adipogenesis-related gene PPARγ, which promotes FFA uptake into adipocytes. Yu et al have reported that OA and linoleic acid promote lipid accumulation in adipocytes, probably through regulating PPARγ phosphorylation [ 22 ], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that OA increased the protein expression of the adipogenesis-related gene PPARγ, which promotes FFA uptake into adipocytes. Yu et al have reported that OA and linoleic acid promote lipid accumulation in adipocytes, probably through regulating PPARγ phosphorylation [ 22 ], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…However, high LA diets were correlated with a decrease in p-IKKα/β (relative to other diets) and p-FADD (relative to euthermia), suggesting NFκB signaling is decreased in WAT. High LA diets can induce the expression of other transcription factors such as AP1 that are capable of increasing sod2 gene expression (Miao and St. Clair, 2009;Yu et al, 2017). Therefore, future studies should focus transcription factors other than NFκB to help explain the increase in sod2 expression in WAT from dormice fed a high LA diet.…”
Section: Resultsmentioning
confidence: 99%
“…Turner PA et al considered that linoleic acid supplementation resulted in enhanced adipogenesis (Turner et al, 2018). The study of Yu C et al also suggested Linoleic acid signi cantly promoted lipid accumulation, probably by regulating PPARγ phosphorylation in adipocytes (Yu et al, 2017). As a consequence, excessive accumulation of linoleic acid might exacerbates FHN through increasing adipogenesis.…”
Section: Biomarker Analysismentioning
confidence: 99%